The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1177/00220345950740110701
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution and Analytical Electron Microscopic Studies of New Crystals Induced by a Bioactive Ceramic (Diopside)

Abstract: Diopside has been developed for use in dental root implants and for the filling of bone defects. In previous studies, diopside developed hydroxyapatite (HA) on its surface and achieved a direct bond with bone. The purpose of this study was to investigate the mechanism of crystal formation on the diopside surface. We ultrastructurally evaluated the interface between new diopside-induced crystals and diopside. Specimens were prepared in three experiments: (1) Granular diopside was immersed in simulated body flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 15 publications
5
39
0
Order By: Relevance
“…Also, Tomson et al (1977) have found that the new mineral formed in dentine has a stoichiometry close to OCP. Other studies using Ca:P ratio measurements completed by morphology analyses (LeGeros et al, 1988;Miake et al, 1995), equidistance measurements (Weiss et al, 1981;Tohda et al, 1997), defect exploration in synthetic tissue (Nelson et al, 1986) or in biological tissue ) also came to the conclusion that OCP should be present in speci®c situations as a transitory precursor of HA. In the last 35 years OCP has more often been found in pathological situations such as in dental calculi (Kodaka & Miake, 1991;Kodaka et al, 1992) or in experimental stimulation of osteogenesis (Suzuki et al, 1991;Sasano et al, 1995), as the formation and stabilization of OCP is facilitated by a low pH value and a temperature increase (LeGeros et al, 1984;Johnsson & Nancollas, 1992).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, Tomson et al (1977) have found that the new mineral formed in dentine has a stoichiometry close to OCP. Other studies using Ca:P ratio measurements completed by morphology analyses (LeGeros et al, 1988;Miake et al, 1995), equidistance measurements (Weiss et al, 1981;Tohda et al, 1997), defect exploration in synthetic tissue (Nelson et al, 1986) or in biological tissue ) also came to the conclusion that OCP should be present in speci®c situations as a transitory precursor of HA. In the last 35 years OCP has more often been found in pathological situations such as in dental calculi (Kodaka & Miake, 1991;Kodaka et al, 1992) or in experimental stimulation of osteogenesis (Suzuki et al, 1991;Sasano et al, 1995), as the formation and stabilization of OCP is facilitated by a low pH value and a temperature increase (LeGeros et al, 1984;Johnsson & Nancollas, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Until now, the only experimental indication for the existence of OCP in calcifying bones and teeth was given by Raman spectroscopy of extracellular matrix vesicles (Sauer et al, 1994) where the ®rst distinct mineral observed had phosphate bonds similar to those found in OCP but clearly different from ACP and HA. Other indirect methods based on Ca:P ratio measurements (Kodaka & Miake, 1991;Kodaka et al, 1992;Paschalis et al, 1996) or morphology analyses (LeGeros et al, 1988;Miake et al, 1995) and equidistance measurements (Weiss et al, 1981;Tohda et al, 1997) were used to explore the possible presence of OCP in calci®ed tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, L. L. Hench seems to indicate that bioactive materials can be obtained with compositions based on the CaO-SiO 2 system rather than in the CaO-P 2 O 5 . Taking into account these observations, Noami et al [79,80] and De Aza et al [81][82][83][84][85][86][87][88][89][90][91][92] have shown that two polycrystalline chain silicate materials: diopside and wollastonite are also bioactives.…”
Section: Bioactive Ceramicsmentioning
confidence: 99%
“…Nakajima et al has developed Mg containing CaO-SiO 2-based diopside (CaMgSi 2 O 6 ) ceramics to be used as biomaterials and has found that the diopside has the ability to form hydroxyapatite in SBF and could close bond to the bone tissue when implanted in rabbits [24,25]. Furthermore, in-vitro and in-vivo studies by Nonami and Miake et al, they have confirmed that the diopside possesses good bioactivity with encountered mechanical properties compared with hydroxyapatite and wollastonite ceramics [26,27]. However, its degradation was extremely low.…”
Section: Bioactivity Investigations With Calcia Magnesia Basedmentioning
confidence: 99%